Primary pulmonary tumours of neurogenic origin. Issue 12 (December 1983) - Roviaro, G; Montorsi, M; Varoli, F; Binda, R; Cecchetto, A
Abstract : Primary intrapulmonary neurogenic tumours are extremely rare. In a series of 1664 patients with pulmonary neoplasms observed during 1967-80 only four such tumours were identified (0.2%). All four patients underwent surgical excision. The histological diagnosis was benign neurilemmoma in three cases and malignant schwannoma in the fourth. The patients with neurilemmoma are alive and well four to 12 years after surgery, but the patient with malignant schwannoma died from metastatic spread of the tumour four months after surgery. No association with von Recklinghausen's disease was observed. Macroscopic and microscopic features generally lead to a correct diagnosis in benign types, but the histological diagnosis of malignant schwannoma may present some difficulties and requires the establishment of a definite origin in a nervous structure, identification of benign neurofibroma in different areas of the same tumour, and a high density of cells with appreciable pleomorphism, with mitosis and atypia. Benign tumours carry a good prognosis with little tendency to recur, but malignant schwannoma has a high invasive tendency and is associated with a low survival rate.